Current challenges and progress in global management, research, science and policy: Eleventh International Conference on Marine Bioinvasions (ICMB-XI) - Amy E. Fowler; Alejandro Bortolus; João Canning-Clode; Tamara B. Robinson; Thomas W. Therriault (Aquatic Invasions)
The Eleventh International Conference on Marine Bioinvasions (ICMB-XI), held May 15–19, 2023, in Baltimore, Maryland, USA, convened 213 attendees from 24 countries to discuss the challenges and advancements in managing marine non-indigenous species (NIS). The conference emphasized the urgent need for international collaboration to address the increasing threats posed by marine bioinvasions, which transcend geopolitical boundaries. Participants explored six key themes through 119 oral presentations, 37 posters, and six keynote speakers, providing a platform for researchers, policymakers, and industry professionals to exchange knowledge and strategies. Notably, ICMB-XI implemented the first Code of Conduct for the Society for the Study of Marine Bioinvasions, promoting inclusivity and ethical scientific discourse. Here, we review articles published in Aquatic Invasions and Management of Biological Invasions based on research presented at ICMB-XI. Studies highlighted novel findings on species settlement dynamics, NIS ecological impacts, and advancements in detection methods such as environmental DNA monitoring. Research also examined the role of climate change in facilitating NIS, the influence of biofouling on NIS establishment, and the expansion of NIS into new ecological niches. Beyond scientific discussions, ICMB-XI celebrated the intersection of art and science through a collaboration with artist April Flanders, whose work communicated the impacts of marine invasions to broader audiences. The conference also provided travel awards and student achievement prizes to support early-career scientists. As ICMB-XI concluded, participants reinforced the need for sustained, large-scale efforts to mitigate marine bioinvasions through enhanced research, policy integration, and cross-sector collaboration. The next ICMB, scheduled for 2025 in Madeira, Portugal, aims to continue advancing the field and fostering international partnerships in marine bioinvasion management.